Fluid Flow Regimes Analysis on Drilling Fluid Circulation for Cuttings Lifting in Vertical Drilling Oil Wells - Isnani Agriandita; Ismanu Yudiantoro; Niken Ayoba NR (Journal of Physics and Its Applications, 2023)
Fluid Flow during the circulation of the drilling fluid is an important parameter that affects the process of successful lifting of cuttings during drilling activities. Researcher analyzed the regimes of the drilling fluid flow in vertical drilling wells through the analysis of the velocity calculation of the drilling fluid in the pipeline at conditions in the Drillpipe (v DP) of 21.11791 fps and in drill collar of (v DC) is 42.98293 fps, the velocity of drilling fluid in the annulus between the Casing and the Drill pipe is 1.14993 fps, 1.373781 fps between Open Hole and Drill pipe, and 1.594947 fps between Open Hole and Drill Collar, the critical velocity of drilling fluid in the pipeline and in the annulus, Reynolds number in the pipeline is 15986.36, inside Drill Collar of 22807.21, and in the annular between the Casing and the Drill pipe is 2847.435, between Open Hole and Drill pipe 3037.264, and 2679.938 between Open Hole and Drill Collar, and the velocity at which the drill cutting drops when in the annulus in all three zones is 0.14914 fps. The results of the analysis of fluid flow that occurs are found that in the pipe there is a turbulent flow and in the annulus a laminar flow occurs. In addition, the results of the analysis of the comparison between the velocity of the drilling fluid in the annulus and greater than the velocity of descent of the cuttings show that the cuttings can be lifted by the drilling fluid successfully. This indicates that the fluid lifting process is successful.